Techniques Used for Analyzing Microplastics, Antimicrobial Resistance and Microbial Community Composition: A Mini-Review - Bartkova, Simona; Kahru, Anne; Heinlaan, Margit; Scheler, Ott (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is a global health threat. Antibiotics, heavy metals and microplastics are environmental pollutants that together potentially have a positive synergetic effect on the development, persistence, transport and ecology of antibiotic resistant bacteria in the environment. To evaluate this, a wide array of experimental methods would be needed to quantify the occurrence of antibiotics, heavy metals and microplastics as well as associated microbial communities in the natural environment. In this mini-review, we outline the current technologies used to characterize microplastics based ecosystems termed “plastisphere” and their AMR promoting elements (antibiotics, heavy metals and microbial inhabitants) and highlight emerging technologies that could be useful for systems-level investigations of AMR in the plastisphere.